Penataan Kelembagaan Keamanan dan Keselamatan Maritim Indonesia - Nugraha, Harry Setya; Grizelda (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This research aims to unravel the consequences of the acceptance of the concept of Indonesia as an archipelagic state, because the increasing size of Indonesian waters triggers the responsibility of the state to ensure that its territorial waters are free from the threat of maritime challenges, disturbances and obstacles (ATGH). State institutions in Indonesia's territorial waters are currently multisectoral, which has led to widespread problems and negative impacts, because Indonesia's maritime security and safety institutions are not well organized. If left unchecked, Indonesia will not only be unable to play a role and contribute much to maintaining global maritime security and safety. It will also bury its dream of becoming the world's maritime axis. The three main issues in this research are how is the regulation of security and safety of marine areas in terms of international law of the sea? What is the urgency of structuring maritime security and safety institutions in Indonesia? What political policies can the government take to organize maritime security and safety institutions in Indonesia? The type of research used to answer these issues is a normative juridical research method with 2 (two) approaches, namely a statutory approach, and a conceptual approach. This research concludes that, first, the consequence of Indonesia's status as an archipelagic state gives Indonesia the authority to regulate its territorial waters in accordance with the provisions of UNCLOS 1982. Second, there are 3 (three) main reasons for the need for structuring Indonesia's maritime security and safety institutions. Starting from philosophical, sociological and political reasons. Third, the political policy that needs to be taken in order to organize Indonesia's maritime security and safety institutions is to form an Omnibus law on the Law on Marine Security and Safety or the Law on the Marine Security Agency.